2013
DOI: 10.1103/physreve.87.062815
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of spiral formation in heterogeneous discretized excitable media

Abstract: Spiral waves on excitable media strongly influence the functions of living systems in both a positive and negative way. The spiral formation mechanism has thus been one of the major themes in the field of reaction-diffusion systems. Although the widely believed origin of spiral waves is the interaction of traveling waves, the heterogeneity of an excitable medium has recently been suggested as a probable cause. We suggest one possible origin of spiral waves using a Belousov-Zhabotinsky reaction and a discretize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Our numerical results showed unidirectional propagation always appeared at the spiral core as reported on the previous paper (Kinoshita et al, 2013). To clarify the cause of unidirectional behavior, we focused on the inhibitor concentration around the path and found a spatial asymmetric profile.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Our numerical results showed unidirectional propagation always appeared at the spiral core as reported on the previous paper (Kinoshita et al, 2013). To clarify the cause of unidirectional behavior, we focused on the inhibitor concentration around the path and found a spatial asymmetric profile.…”
supporting
confidence: 58%
“…These cells were placed randomly in BZ reaction field (see Supplement). Figure 1 shows the previous results [15], which illustrate that the unidirectional path was generated spontaneously with the spatial heterogeneity of excitability. Although our previous study [15] indicated that certain distributions of suppression cells could spontaneously generate the unidirectional path, the mechanism and the specific structure necessary to create unidirectional path have not been elucidated.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…by spontaneous formation of spirals due to ectopic beats. The accumulation of the heterogeneities in a particular region of the system may generate reentries [18,19] due to the formation of a source-sink mismatch [20,21]. On the other hand, heterogeneities can be also employed as virtual electrodes to generate a large number of new waves to suppress fibrillatory electrical activity [22,23].…”
Section: Introductionmentioning
confidence: 99%